2022
DOI: 10.1186/s12905-022-02083-4
|View full text |Cite
|
Sign up to set email alerts
|

A risk prediction model mediated by genes of APOD/APOC1/SQLE associates with prognosis in cervical cancer

Abstract: Cervical cancer is one of the most common gynecological malignancies. Due to the high heterogeneity of cervical cancer accelerating cancer progression, it is necessary to identify new prognostic markers and treatment regimens for cervical cancer to improve patients’ survival rates. We purpose to construct and verify a risk prediction model for cervical cancer patients. Based on the analysis of data from the Gene Expression Omnibus database (GEO) and The Cancer Genome Atlas (TCGA), differences of genes in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This model comprises nine genes, including three protective genes (APOD, CDHR4, and PCP2) and six risk genes (CALCB, MAFA, NLGN1, SLITRK3, SPDYC, and SPINK8). The prognostic value of apolipoprotein D (APOD) has been demonstrated in various cancers, including cervical cancer [19] and prostate cancer [20]. Recent studies revealed that ApoD-positive patients have better overall survival, and its expression can independently predict breast cancer prognosis irrespective of ERα and AR expression [21].…”
Section: Discussionmentioning
confidence: 99%
“…This model comprises nine genes, including three protective genes (APOD, CDHR4, and PCP2) and six risk genes (CALCB, MAFA, NLGN1, SLITRK3, SPDYC, and SPINK8). The prognostic value of apolipoprotein D (APOD) has been demonstrated in various cancers, including cervical cancer [19] and prostate cancer [20]. Recent studies revealed that ApoD-positive patients have better overall survival, and its expression can independently predict breast cancer prognosis irrespective of ERα and AR expression [21].…”
Section: Discussionmentioning
confidence: 99%
“…GJA1 was considered to potentially play a significant role in melanoma and could predict patients’ response to PD-1 immunotherapy [ 62 ]. APOD was used to construct a risk model for predicting immune infiltration and immunotherapy in cervical cancer [ 63 ]. In various studies, distinct immunotherapy drugs have demonstrated varying efficacy among GC patients at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…This model comprises nine genes, including three protective genes (APOD, CDHR4, and PCP2) and six risk genes (CALCB, MAFA, NLGN1, SLITRK3, SPDYC, and SPINK8). The prognostic value of apolipoprotein D (APOD) has been demonstrated in various cancers, including cervical cancer [19] and prostate cancer [20]. Recent studies revealed that ApoD-positive patients have better overall survival, and its expression can independently predict breast cancer prognosis irrespective of ERα and AR expression [21].…”
Section: Discussionmentioning
confidence: 99%